Terrorist use of the internet by the numbers: quantifying behaviors, patterns, and processes - Gill, Paul (Criminology & public policy, 2017)
Public interest and policy debates surrounding the role of the Internet in terrorist activities is increasing. Criminology has said very little on the matter. By using a unique data set of 223 convicted United Kingdom–based terrorists, this article focuses on how they used the Internet in the commission of their crimes. As most samples of terrorist offenders vary in terms of capabilities (lone‐actor vs. group offenders) and criminal sophistication (improvised explosive devices vs. stabbings), we tested whether the affordances they sought from the Internet significantly differed. The results suggest that extreme‐right‐wing individuals, those who planned an attack (as opposed to merely providing material support), conducted a lethal attack, committed an improvised explosive device (IED) attack, committed an armed assault, acted within a cell, attempted to recruit others, and engaged in nonvirtual network activities and nonvirtual place interactions were significantly more likely to learn online compared with those who did not engage in these behaviors. Those undertaking unarmed assaults were significantly less likely to display online learning. The results also suggested that extreme‐right‐wing individuals who perpetrated an IED attack, associated with a wider network, attempted to recruit others, and engaged in nonvirtual network activities and nonvirtual place interactions were significantly more likely to communicate online with co‐ideologue.